Republic of Madagascar : Fifth Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Republic of Madagascar's Fifth Review Under the Extended Credit Facility (ECF) Arrangement. Madagascar's performance under its economic program supported by the ECF arrangement has remained generally strong. Discussions focused on the recently adopted 2019 revised budget law, which reflects the priorities of the new government and accommodates additional investment spending without undermining the main program objectives, as well as on the two main challenges relating to fuel pricing and the losses of the public utility JIRAMA. Other issues discussed included the strengthening of social safety nets, reforms in the financial sector, and progress on governance. Growth has been solid, inflation has been moderate, and the external position has remained robust. Going forward, the authorities' continued commitment to strong policies and an ambitious structural reform agenda will be key to mitigating internal and external risks, strengthening macroeconomic stability, and achieving higher, sustainable, and inclusive growth.